Memaknai Praktik Tradisi Ritual Masyarakat Muslim Sumenep - Achmad Mulyadi (Endogami: Jurnal Ilmiah Kajian Antropologi, 2018)
THIS -- paper seeks to reveal the meaning of tradition in the Muslim’s ritual in Sumenep Madura which is understood as a local or popular ritual, associated with the determination of the calendar in Islam. This ritual, when expressed and understood in practice, is always based on the popularization of calendar names in local-based Islam with certain insights and meanings. With this deductive-inductive explorative approach, this paper explain to three popular ritual praxis of the Sumenep Madurese. Firstly, the practice of the death ritual that was intended as a repentance to God for self and “al-marhum”, ties the brotherhood, and effective for Islamic preaching. Secondly, the ritual practice of “Peret Kandung” is a ritual of the first pregnancy for husband and wife entering the seventh month which is meant as a symbol of purification, so that the born child will survive and truly become sholeh child who boast of parents. Third, “sonat ritual” is a continuation of initiation ritual in Sumenep only for boys which is meant as a ritual as well as da'wah media for islamization.